Enhancing antioxidant activity and quality of Triadica cochinchinensis honey via an automated temperature-humidity controlled cabinet - Jiang, Huizhi; Chen, Weixuan; Jiang, Wujun; Liu, Feng; Wu, Xiaobo; Yan, Weiyu; He, Xujiang; Zeng, Zhijiang (Frontiers in Nutrition, 2025)
Honey, a key beekeeping product, is rich in antioxidants and bioactive compounds, offering antimicrobial, anti-inflammatory and health-promoting properties. The water content of honey is directly correlated with its quality. However, Triadica cochinchinensis honey (TCH), produced in high humidity regions, is frequently at risk of fermentation and spoilage due to excessive water content. A dewatering method using an automated, temperature- and humidity-controlled honey cabinet was applied to address this issue and investigate its effects on TCH. After 96 h of treatment, the water content of TCH capped honeycombs effectively reduced to below 18%. Meanwhile, most physicochemical parameters, volatile compounds and chemical compositions largely remained unchanged, thereby preserving their nutritional value and flavor. Moreover, phenolics and flavonoids levels significantly increased by 15.83 and 25.42%, respectively, thereby enhancing the honey’s antioxidant capacity. Our results indicated that this method can significantly enhance maturity and improve the quality of TCH, providing reference value for other honey produced in high humidity regions. The utilization of honey cabinets can enhance the market value of honey in these regions, and consumers can benefit from higher-quality honey with greater biological activity.